Cryptocurrency competition: An empirical test of Hayek's vision of private monies - Fabian Mayer; Peter Bofinger (University of Würzburg, Department of Economics, 2023)
We investigate monopolistic tendencies and the intensity of currency competition on the crypto market in the light of Hayek's "Denationalization of money". Interestingly, Hayek never considered differentiation and specialization by innovative private currencies could lead lasting currency competition instead of network effects. We argue that competition between private currencies could run on different functions of money, especially the function as a store of value and that as a means of exchange, which partly explains the differences in the set-up of private currencies that Hayek demanded and that of cryptocurrencies. Drawing on a large sample of 101 cryptocurrencies and a time frame from 2016 to 2022, we empirically examine the evolution and degree of competition on the crypto market, also taking changes in general crypto market structure into account. We find that competition is strong for unpegged cryptocurrencies that mostly compete as a speculative store of value. Competition is also strong for stablecoins when competing as a stable store of value. Competition is much less pronounced for the function as a means of exchange and network effects and monopolistic tendencies are more likely to be present on this sub-market.
Keywords: B25; D40; E42; E50; E51; L11; 330; Hayek; Cryptocurrencies; Functions of Money; Currency Competition; NetworkEffects; Monopol